Influence of amyloid deposition on the interaction between tau and glucose metabolism. (December 2021) - Nowell, Joseph; Raza, Sanara; Livingston, Nicholas R.; Crook, Harry; Young, Megan; Edison, Paul
Abstract: Background: Pathological hallmarks of Alzheimer's disease include the formation of extracellular Aβ plaques and intracellular neurofibrillary tau tangles, which with recent PET imaging advances can be assessed in vivo . Accumulation of tau has been closely linked to metabolic abnormalities in PET imaging studies, with inverse associations between tau deposition and glucose metabolism. This study aimed to assess whether the association between [18F]FDG and [18F]AV1451 in cognitively impaired patients is dependent on the presence of significant amyloid pathology. Method: 240 patients with mild cognitive impairment or Alzheimer's disease (Mean age = 74.5 years, SD = 8.03) were evaluated from the Alzheimer's Disease Neuroimaging Initiative (adni.loni.usc.edu). All participants completed a T1‐weighted MPRAGE MRI, amyloid ([18F]AV45 or [18F]florbetaben), [18F]AV1451 and [18F]FDG scans. Standard uptake ratio values were calculated in SPM12 to identify the glucose metabolic rate and tau deposition within cortical regions. Amyloid status (Aβ‐positive/Aβ‐negative) was determined from processed data using a whole brain cerebellar ratio with a cut‐off value of 1.11 ([18F]AV45) and 1.08 ([18F)florbetaben). Pearson's correlation coefficients were calculated to assess the relationship between imaging modalities. Result: There were significant negative associations between AV1451 and FDG tracer uptake in the medial temporal lobe (r = ‐0.389, p <0 .001), occipital lobe (r = ‐0.276, p = 0.001), parietal lobe (r = ‐0.209, p = 0.014), and posterior cingulate (r = ‐0.245, p = 0.004) in Aβ‐positive patients. Similarly, a strong negative relationship was observed between the imaging modalities in Aβ‐negative patients in the medial temporal lobe (r = ‐0.345, p < 0.001), however a significant positive association was also observed in the anterior cingulate cortex (r = 0.350, p < 0.001). Conclusion: This study demonstrated that [18]FDG and [18F]AV1451 tracers have strong regional signal associations in patients with cognitive impairment. The results indicate that tau has a detrimental effect on glucose metabolism in the medial temporal lobe, independent of significant amyloid plaque formation. In patients determined as amyloid‐negative, we may be observing some compensatory regional increase in glucose metabolism in the early stages of tau accumulation.